Original paperPharmacotherapy of diabetes type 2 and acute hyperglycaemia-related alterations of T-lymphocytes immunophenotype in peripheral blood - Dworacka, Marzena; Winiarska, Hanna; Borowska, Magdalena; Dworacki, Grzegorz (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2006)
Aim: We aimed to evaluate the influence of type 2 diabetes, metabolic control and different types of pharmacotherapy on potentially proatherogenic alterations in peripheral blood T-lymphocytes. Materials and methods: We studied 15 healthy subjects and 97 type 2 diabetic patients receiving sulfonylureas (SU), conventional insulin therapy (INS), sulfonylureas in combination with insulin (SU+INS) or diet only (NF). In every patient, fasting glucose, HbA1c and lipid profile were assayed, C-peptide serum level was assayed as a marker of beta-cells function and 1,5-anhydro-D-glucitol concentration in plasma – as a parameter reflecting acute hyperglycaemic episodes. Cell surface receptors – CD3+, CD4+, CD8+, CD8+28+, CD8+28- were detected by direct immunofluorescence evaluated by flow cytometry. Results: There was an increase in CD3+, CD4+, CD8+28+, CD8+28- cell count in diabetic group in comparison to healthy controls. CD4+ receptor expression was mainly determined by 1,5-AG plasma level, while CD8+28- receptors expression was dependent on both: 1,5-AG plasma levels and type of pharmacotherapy. Conclusions: These data show that in type 2 diabetic patients the count of helper T-cells and cytotoxic-supressor T-cells CD8+28- increase in relation to acute hyperglycaemia. The increase in cytotoxic-supressor T-cells CD8+28- was associated with type of pharmacotherapy, as well. Considering alterations in T-cells subpopulations SU-treatment seems to be more beneficial than conventional INS therapy or therapy with SU+INS combination.